(untitled) (Research, Society and Development, 2022)
Chronic kidney disease is characterized as a public health problem in Brazil and worldwide. It gradually compromises renal function, presents a progressive, irreversible character and, for most cases, hemodialysis is a treatment option. The objective of the research was to evaluate the nutritional profile of patients on hemodialysis in a nephrology clinic in the western region of Paraná. This is a cross-sectional study, carried out with 101 patients. The variables gender, age, etiology of chronic kidney disease and time on hemodialysis were collected from medical records and recorded in a form developed by the researchers, based on the literature. Nutritional assessments were performed. For descriptive statistical analysis, Chi-Square and Student’s t tests were used. The patients’ mean body mass index indicated overweight. Systemic arterial hypertension was the cause of chronic kidney disease in most patients. The prevalence of protein-energy malnutrition was 39.60% by the arm muscle circumference, 33.66% by the arm circumference, 29.70% by the Modified Global Subjective Assessment and 25.74% by the body mass index. The treatment time possibly contributes to the depletion of muscle mass and worsening of the nutritional status of these patients. Therefore, the nutritional assessment of hemodialysis patients remains an important challenge, in order to better understand the nutritional and metabolic changes presented and to act in the maintenance or recovery of health, minimizing their damage, as well as reducing initial morbidity and mortality.